1967
DOI: 10.1017/s0025315400035281
|View full text |Cite
|
Sign up to set email alerts
|

A Seasonal Cycle in the Testis of the Spurdog, Squalus Acanthias, and the Sites of 3β-Hydroxysteroid Dehydrogenase Activity

Abstract: The histology of the spurdog (Squalus acanthias L.) testis was observed through a complete annual cycle. The maximum sperm accumulation coincided with the breeding time as defined by the biennial female cycle. Degeneration of spermatogonia was observed following breeding. The band of degenerate germinal ampullae was identical to that described as occurring in Scyliorhinus canicula (L.) following pituitary ventral lobectomy. This suggested a resting phase in the production of a specific pituitary gonadotrophin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 12 publications
6
27
0
Order By: Relevance
“…that of the ZD, a finding that is consistent with the TUNEL analysis (McClusky 2005). The ZD, which is thus labelled by both the TUNEL and the AO techniques, represents the past winter's M-PrM cysts that ceased any further development (McClusky 2005), presumably as a result of a natural break in pituitary gonadotropin support during the winter months (Simpson and Wardle 1967;Dobson and Dodd 1977). AO-labelling varies from discrete punctate bright green labelling (in mid-stage PrM cysts), which indicates an early stage of germ cell apoptosis, to intense yellow-orange labelling observed in flattened ZD cysts, which indicates an advanced stage of apoptosis and labelling associated with the phagocytosed germ cell corpses in Sertoli cells.…”
Section: Discussionsupporting
confidence: 67%
“…that of the ZD, a finding that is consistent with the TUNEL analysis (McClusky 2005). The ZD, which is thus labelled by both the TUNEL and the AO techniques, represents the past winter's M-PrM cysts that ceased any further development (McClusky 2005), presumably as a result of a natural break in pituitary gonadotropin support during the winter months (Simpson and Wardle 1967;Dobson and Dodd 1977). AO-labelling varies from discrete punctate bright green labelling (in mid-stage PrM cysts), which indicates an early stage of germ cell apoptosis, to intense yellow-orange labelling observed in flattened ZD cysts, which indicates an advanced stage of apoptosis and labelling associated with the phagocytosed germ cell corpses in Sertoli cells.…”
Section: Discussionsupporting
confidence: 67%
“…Follow-up biochemical and in situ fluorescence analyses (McClusky et al 1996) to an initial report of Simpson & Wardle (1967), which described a zone comprising several layers of degenerating germinal tissue that first appears naturally in May in S. acanthias at the spermatogonia-spermatocyte transition, confirmed the mode of death in this tissue as apoptosis. Since it has always been assumed that the month of May also marked the onset of the spermatogenically active period in Squalus , Piferrer & Callard 1995, the observation of such a large stage-specific loss of testicular cells during presumed normal testicular recrudescence was indeed intriguing.…”
Section: Introductionmentioning
confidence: 89%
“…As summarized in Table 1, staging criteria were based on (a) position of the cyst in the testis cross-section relative to the germinal ridge (maturational order), (b) cyst diameter and (c) cyst organization with respect to relative numbers and positions of germ-cell versus Sertoli-cell nuclei, as Cell cycle and apoptosis in the shark testis 91 www.reproduction-online.org described in earlier studies of this and other dogfish species (Stanley 1966, Simpson & Wardle 1967, Holstein 1969. For example, based on actual cell counts per spermatocyst, Sertoli cells have been reported to undergo nine, and germ cells an additional four, mitotic divisions in Squalus (Holstein 1969).…”
Section: Staging Criteriamentioning
confidence: 99%
“…Histochemical data have shown that 3ß-hydroxysteroid dehydrogenase (3ß-HSD) activity is local¬ ized in the cytoplasm of the Sertoli cell of the dogfish (Simpson and Wardle, 1967;Collenot, 1969). Dubois and Callard (1989) have demonstrated 3ß-HSD, hydroxylase/lyase and aromatase activities in Sertoli cells of Squalus acanthias in vitro.…”
Section: Introductionmentioning
confidence: 99%